A critical consideration of ‘mental health and wellbeing’ in education: Thinking about school aims in terms of wellbeing - Norwich, Brahm; Moore, Darren; Stentiford, Lauren; Hall, Dave (British Educational Research Journal, 2022)
This paper examines ideas about mental health, wellbeing and school education to illustrate important issues in the relationship between mental health and education. The Covid crisis has amplified the pre-existing mental health problems of children and young people in England and recognition of the opportunities in schools to address these. The paper gives an overview of child and adolescent mental health services and how they position the role of schools. It examines prominent concepts of mental health and their relationship to wellbeing, setting this in a discussion of ‘mentally healthy’ schools, mental health in special educational needs and whole-school approaches. This analysis shows how the relationship between mental health and wellbeing has not been adequately worked out, using this as the basis for arguing for the dual-factor mental health model which separates mental illness/disorder from wellbeing as two related dimensions. The paper then translates the dual-factor model into a two-dimensional framework that represents the distinctive but related aims of school education (wellbeing promotion) and mental health services (preventing, coping, helping mental health difficulties). This framework involves a complex conception of wellbeing, with schools playing an important role in promoting wellbeing (beyond emotional wellbeing), tiered models and establishing school-wide social emotional learning. It is about a whole-school curriculum approach that involves considering what is to be learned and how it is taught. It contributes to a more nuanced concept of wellbeing that has a place for meaningful learning and challenge.
Keywords: mental health; school education aims; special educational needs; wellbeing